Understanding Phonetics: The Science That Helps Us Understand How Humans Speak - Harahap, Fitri Handayani; Darmila, Sulis; Wicaksono, Teguh Wahyu (EDUCTUM: Journal Research, 2025)
Phonetics is a branch of linguistics that studies human speech sounds from articulatory, acoustic, and auditory aspects. This study aims to provide a comprehensive understanding of the basic concepts of phonetics, its scope, and its role and application in linguistics, language education, technology, and social life. This study uses a literature study method by reviewing various scientific sources in the form of relevant books and journal articles. Data are analyzed descriptively qualitatively to reveal the position of phonetics as a foundation in the analysis of language sounds. The results of the study indicate that phonetics plays a fundamental role in explaining the process of sound production, the physical characteristics of sound, and the mechanisms of human auditory perception. In addition to serving as a basis for the study of phonology, phonetics also contributes significantly to language learning, speech therapy, the development of speech recognition technology, and forensic analysis. Thus, phonetics is not only theoretical, but also applicable and interdisciplinary, and plays a vital role in understanding language as a complex and dynamic human communication system.